2014
DOI: 10.1021/jp502123n
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of the Förster Radius in Colloidal Quantum Dot Solids

Abstract: Excitonic energy transfer among colloidal nanocrystal quantum dots (QDs) is responsible for exciton transport in many QD optoelectronic devices. While Förster theory has successfully accounted for the distance scaling of energy transfer in many QD systems, the overall magnitude of the Förster radius in close-packed QD solids remains an open question. Here, we use spectrally resolved transient photoluminescence quenching to measure the magnitude of the Förster radius in blended donor–acceptor QD assemblies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 50 publications
13
106
0
Order By: Relevance
“…[41][42][43][44][45][46] Studying the motion of neutral excitons, however, is a far more challenging task. To date, the exciton diffusion in NC solids has been investigated via steady-state and time-resolved spectroscopy methods 36,44,[47][48][49][50][51][52] while their 4 diffraction limited spatial profile has been visualized through optical microcopy. 35 Despite these efforts, the exact nature of the exciton dissociation mechanism as well as exciton diffusion trajectories in nanocrystal solids still remain poorly understood.…”
mentioning
confidence: 99%
“…[41][42][43][44][45][46] Studying the motion of neutral excitons, however, is a far more challenging task. To date, the exciton diffusion in NC solids has been investigated via steady-state and time-resolved spectroscopy methods 36,44,[47][48][49][50][51][52] while their 4 diffraction limited spatial profile has been visualized through optical microcopy. 35 Despite these efforts, the exact nature of the exciton dissociation mechanism as well as exciton diffusion trajectories in nanocrystal solids still remain poorly understood.…”
mentioning
confidence: 99%
“…For FRET, K ET is close to unity when r 0.5R 0 and decreases to zero when r 1.5R 0 [26]. The 18-nm barrier is much wider than R 0 = 4 ÷ 10 nm reported previously for II-VI nanocrystals [28,38,49], and FRET should be virtually suppressed at such a distance. We use two values (400 and 550 ps) of τ 0 D to show the influence of its variation.…”
Section: Confirmation Of Fret By Pl Decay Studies Plmentioning
confidence: 93%
“…Notably, the observed ET rate was about an order of magnitude greater than the one reported by Kagan et al 38 Recently, Tisdale group has reported the distance dependence of the energy transfer rate between the donor-and acceptor-type nanocrystals. 50 To this end, QD films were fabricated by depositing homogeneous blends of small and large diameter CdSe/CdZnS core/shell NCs, using either long-chain (octadecylphosphonic acid) or short-chain (benzylphosphonic acid) crosslinking ligands. Based on the observed modulation of the acceptor emission, it was concluded that the non-radiative energy transfer between donor and acceptor QDs deviates from the Förster type, 1/R 6 , scaling.…”
Section: Bulk Quenchingmentioning
confidence: 99%
“…However, with recent advances in film fabrication techniques and surface passivation strategies, the use of PL-based techniques to studying the excited state dynamics in QD solids has witnessed a revival, with an ever-increasing number of publications appearing in recent years. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] These days, the complexity of PL-based methods for probing the excitation dynamics of artificial solids continues to evolve. By offering both temporal and spatial profile of the energy flow in artificial solids, these techniques become increasingly valuable in gauging important charge transport and exciton diffusion characteristics.…”
mentioning
confidence: 99%